Participatory Planning for Climate Compatible Development in Maputo, Mozambique / Planeamento participativo para o desenvolvimento compatível com o clima em Maputo, Moçambique - Castán Broto, Vanesa (UCL Press, 2015)
Participatory Planning for Climate Compatible Development in Maputo, Mozambique is a practitioners' handbook that builds upon the experience of a pilot project that was awarded the United Nations 'Lighthouse Activity' Award. Building upon a long scholarly tradition of participatory planning, this dual-language (English/Portuguese) book addresses crucial questions about the relevance of citizen participation in planning for climate compatible development and argues that citizens have knowledge and access to resources that enable them to develop a sustainable vision for their community. In order to do so, the author proposes a Participatory Action Planning methodology to organise communities, and also advances mechanisms for institutional development through partnerships.